Magpie murders ebook - Horowitz, Anthony (Magpie Murders, 2017)
Don't miss Magpie Murders on PBS's MASTERPIECE Mystery! "A double puzzle for puzzle fans, who don't often get the classicism they want from contemporary thrillers." —Janet Maslin, The New York Times New York Times Bestseller | Winner of the Macavity Award for Best Novel | NPR Best Book of the Year | Washington Post Best Book of the Year | Esquire Best Book of the Year From the New York Times bestselling author of Moriarty and Trigger Mortis, this fiendishly brilliant, riveting thriller weaves a classic whodunit worthy of Agatha Christie into a chilling, ingeniously original modern-day mystery. When editor Susan Ryeland is given the manuscript of Alan Conway's latest novel, she has no reason to think it will be much different from any of his others. After working with the bestselling crime writer for years, she's intimately familiar with his detective, Atticus Pünd, who solves mysteries disturbing sleepy English villages. An homage to queens of classic British crime such as Agatha Christie and Dorothy Sayers, Alan's traditional formula has proved hugely successful. So successful that Susan must continue to put up with his troubling behavior if she wants to keep her job. Conway's latest tale has Atticus Pünd investigating a murder at Pye Hall, a local manor house. Yes, there are dead bodies and a host of intriguing suspects, but the more Susan reads, the more she's convinced that there is another story hidden in the pages of the manuscript: one of real-life jealousy, greed, ruthless ambition, and murder. Masterful, clever, and relentlessly suspenseful, Magpie Murders is a deviously dark take on vintage English crime fiction in which the reader becomes the detective.